Results on fractal measure of some sets - Barbulescu, A. (Інститут математики НАН України, 2007)
The fractal dimensions are very important characteristics of fractal sets. A problem which arises in the study of fractal sets is the determination of their dimensions. The Hausdorf dimension is dfficult to be determined, even if the box dimensions can be computed. In this article we present some relations between these types of measures and we estimate them for some sets.